Dasar Negara dan Hukum Dasar: Suatu Telaahan Yuridis atas Relasi Pancasila dan UUD 1945 - Udiyo Basuki (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
The basis of the State is the attitude of life or outlook onlife which is a state philosophy (political philosophy) which isdomiciled as the source of all sources of law or sources oforderly law in a country. Whereas the Basic Law is the basicrules which are used as the basis and source for the applicationof all laws or regulations or legislation in the administration ofa country's government. In the spirit and pace of constitutionaldynamics, Pancasila as the Foundation of the Indonesian Statehas a very close relationship with the Basic Law or theIndonesian constitution, the 1945 Constitution, especially in thiscase with the Preambulation of the 1945 Constitution. Apartfrom the formulation of the Pancasila contained in thePreamble to the 1945 Constitution, the two are inseparable fromeach other, both are also regarded as basic norms, as sources ofpositive law. The basic legal formulation in the articles in theBody of the 1945 Constitution is emanating from the norms inthe Preamble to the 1945 Constitution and Pancasila. Theprinciples of Pancasila are contained in and are part of thePreamble to the 1945 Constitution.Keywords: state foundation, basic law, Pancasila, 1945Constitution